Modeling Techniques, Seismic Performance, and the Application of Rocking Shallow Foundations: A Review - Musab Aied Qissab Al-Janabi; Duaa Al-Jeznawi; Luís Filipe Almeida Bernardo (CivilEng, 2024)
The intriguing rocking behavior of foundations has attracted the attention of both researchers and professionals, owing to its beneficial characteristics such as energy absorption and self-adjusting capability. This paper offers a thorough examination of various modeling techniques, seismic performance evaluation methods, and the practical application of innovative rocking shallow foundations. While conventional fixed-base designs can absorb seismic energy, they often suffer from lasting damage due to residual deformation. In contrast, rocking foundation structures facilitate controlled rocking movements by loosening the connection between the structure and the foundation, thereby enhancing overall stability. Historical studies dating back to the 19th century demonstrate the effectiveness of rocking foundations in reducing seismic impact and ductility demands, leading to cost savings. Furthermore, this paper extends its focus to contemporary considerations, exploring modern modeling techniques, seismic performance assessments, and practical applications for rocking shallow foundations. By highlighting their role in improving structural resilience, this study investigates seismic hazard analysis, geological factors, and site-specific conditions influencing foundation behavior. It covers essential aspects such as dynamic responses and modeling methodologies, drawing insights from real-world case studies. Through a comprehensive review of both numerical and experimental investigations, the article provides a synthesis of current knowledge and identifies avenues for future research.